2016
DOI: 10.7717/peerj.2497
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically crosslinked gelatin hydrogel promotes the proliferation of adipose tissue-derived stromal cells

Abstract: Gelatin hydrogel crosslinked by microbial transglutaminase (mTG) exhibits excellent performance in cell adhesion, proliferation, and differentiation. We examined the gelation time and gel strength of gelatin/mTG hydrogels in various proportions to investigate their physical properties and tested their degradation performances in vitro. Cell morphology and viability of adipose tissue-derived stromal cells (ADSCs) cultured on the 2D gel surface or in 3D hydrogel encapsulation were evaluated by immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 40 publications
6
103
0
Order By: Relevance
“…Previously, measurements of samples of 5% gelatin and comparable amounts of mTG as used here, have shown Young's modulus in the range of ~6 kPa measured on a Solid Analyzer at 37°C without having the sample immersed . Others have shown Young's modulus of 12.4 kPa of 5% gelatin hydrogels where the measurements were performed at room temperature . The lower modulus measured in the stretch setup (Figure ) compared to the rheometer and Solid Analyzer is believed to be caused by swelling of hydrogels in the immersed state.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Previously, measurements of samples of 5% gelatin and comparable amounts of mTG as used here, have shown Young's modulus in the range of ~6 kPa measured on a Solid Analyzer at 37°C without having the sample immersed . Others have shown Young's modulus of 12.4 kPa of 5% gelatin hydrogels where the measurements were performed at room temperature . The lower modulus measured in the stretch setup (Figure ) compared to the rheometer and Solid Analyzer is believed to be caused by swelling of hydrogels in the immersed state.…”
Section: Resultsmentioning
confidence: 55%
“…This reduces time and cost and diminishes the technical difficulties in when casting stretchable hydrogel. Furthermore, mTG is non‐toxic, biocompatible, and is the most studied enzyme in protein‐based crosslinked hydrogels in tissue engineering . The mechanical behavior of gelatin crosslinking with mTG is dependent on the temperature at which the crosslinking is performed.…”
Section: Resultsmentioning
confidence: 99%
“…Since microbial transglutaminase (mTG) cross-links glutamine and lysine via a transamidation reaction, the mechanical properties of the gelatin hydrogel depended on the mTG dosage and the amounts of these molecules as presented by the gelatin concentration. Previous studies reported that the gelation time of mTG gel ranged from~15 s to hours with a constant mTG concentration (10 U g −1 ) [47][48][49] . The microchannel hydrogel induced invasion and M2 polarization of monocytes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation method of primary ADSCs was described in our previous publication (Li et al 2015;Yang et al 2016). Harvested ADSCs were seeded at a density of 1.0 9 10 4 cells/cm 2 on 0.1% gelatin-coated coverslips and placed into six-well tissue-culture plates (TCPs) and incubated at 37°C in a humid 5% CO 2 atmosphere for 24 h. Electrical stimulations were performed using homemade EF bioreactors, as described in our previous publication (Long et al 2011).…”
Section: Electrical Field Stimulation On 2d-culturesmentioning
confidence: 99%